Upaya dan Langkah Strategis Pimpinan Pondok Pesantren dalam Meningkatkan Kualitas Pendidik di Pondok Pesantren Al-Ikhlas Karawang - Maulana, Muhith; Suryana, Sayan; Husein, Ceceng Syarif (Jurnal Ilmiah Wahana Pendidikan, 2024)
The main focus of this research is the efforts and strategic steps used by Islamic boarding school leaders in improving the quality of educators. The purpose of this research is to find out the efforts and strategic steps used by Islamic boarding school leaders in improving the quality of educators. Researchers used a qualitative approach with a descriptive case study design. Data were obtained using observation, interview and documentation techniques. To analyze the data, the researcher followed the steps described by Miles & Hubberman, namely: data reduction, data presentation, and conclusion/verification. Through this investigation, researchers found that in improving the quality of educators at the Al-Ikhlas Karawang Islamic boarding school, the leadership of the Islamic boarding school used 5 strategic efforts and steps. Namely fostering the quality of educators; supervision of the quality of educators; provision of facilities and infrastructure; instilling commitment; and granting allowances. These results indicate that the strategic efforts and steps used by Islamic boarding school leaders have proven to be good and effective in improving the quality of educators at the Al-Ikhlas Karawang Islamic Boarding School.